Pengaruh Naungan Pemberian Nitrogen terhadap Komposisi Kimia Rumput Brachiaria Decumbens, Stapf (Effect of Shading and Nitrogen Fertilizer on Chemical Compotition of Brachiaria Decumbens Stapf) - Mappaona Mappaona; Soedarmadi Hardjosoewignjo; Justika Baharsjah; Ignatius Kismono (Buletin Ilmu Makanan Ternak, 1987)
In tropics climate, growth is so fast that many grasses don't maintain mineral status satisfactory for ruminants nutrition. Several publications showed that plant grown under reduced light intensity contain higher mineral than the open condition. Improving forage quality through nitrogen fertilizer has been well documented since many years ago. To get information the influence of shade and nitrogen fertilizer on the chemical composition of Brachiaria, decumbens, stapf, a split-plot experiment with shade intensity (0, 30 and 60%) as main plot and nitrogen fertilizer (0, 75 and 150 kg/ha) as sub plot was conducted on latosol soil at IPB experimental farm, Tajur-Bogor from April to August 1986.The results showed that nitrogen fertilizer affected N, P and K content significantly. There was interaction between shade and nitrogen in relation to plant N and P content. This meant that the response of the grass to the nitrogen fertilizer differed at various level of shade intensity. Application of the nitrogen fertilizer at 60% shade intensity did not affect the increase of Plant N content. Nitrogen fertilizer increased plant P content significantly at 60% shade intensity, but did not at 0 and 30%. The increased of shade intensity, raised the plant mineral content.